Optimal Buffer-Aided Relaying With Imperfect CSI - Jamali Kooshkghazi, Vahid; Waly, Noha; Zlatanov, Nikola; Schober, Robert (IEEE Communications Letters, 2016)
In this letter, we consider a two-hop relay channel that consists of a source, a half-duplex decode-and-forward relay, and a destination. We derive the optimal buffer-aided relaying policy based on imperfect channel state information (CSI) and under long-term per-node power constraints for the source and the relay. In particular, the proposed protocol determines the optimal state of the relay node, namely, the transmit, receive, or silent state, based on the imperfect CSI of the involved links, the quality of the CSI, and the required acquisition overhead. Our simulation results verify the analysis and reveal that there is an optimal tradeoff between the required acquisition overhead and the quality of the CSI that maximizes the throughput.<br
Keywords: Relays; Throughput; Protocols; Channel estimation; Fading channels; Simulation; Indexes